SISTEM INFORMASI LAYANAN WARTAWAN (SILAW) PADA KEPOLISIAN DAERAH SUMATERA SELATAN - Alif, Syafiq Muhammad; Fenando, Fenando (JURNAL ILMIAH INFORMATIKA, 2025)
The Public Relations Section of the South Sumatra Regional Police has an important role in establishing communication with the media, especially in the process of registering and attending journalists at press release activities. However, the process that is still carried out manually creates various obstacles, such as the accumulation of physical documents, delays in the verification process, the risk of losing data, and the potential for errors in recording attendance. Based on these problems, this study aims to design and implement a web-based Journalist Service Information System (SILAW) to automate all administrative processes involving journalists. The development method used is the prototyping approach, which includes the stages of requirements gathering, prototyping, user evaluation, system coding, and testing. The system was developed using PHP programming language and PhpMyAdmin database. The implementation results show that this system can improve operational efficiency, speed up the registration process, minimize the risk of data loss, and facilitate the process of recording and reporting journalists' attendance. SILAW provides online registration, digital document management, file validation, automatic attendance recording, and systematic activity report generation. With the implementation of this system, the management of relations between PR and media becomes more effective, structured, and responsive. This research makes a real contribution to the digitization of public services in the police environment, and becomes a model that can be applied in similar agencies.